(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In the era of globalization and rapid technological advancement, project management has become a key instrument for organizational success. For joint-stock companies (JSCs), where transparency, shareholder value, and governance play an essential role, project management ensures that corporate objectives are achieved efficiently and sustainably. This paper explores the application of project management within joint-stock companies, focusing on the tourism industry as a practical example. It analyzes theoretical frameworks, discusses challenges and opportunities, and illustrates the role of structured project management through case studies.